2011 IEEE 16th International Workshop on Computer Aided Modeling and Design of Communication Links and Networks (CAMAD) 2011
DOI: 10.1109/camad.2011.5941100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of channel estimation errors on effectiveness of Eigenvector-based jamming for physical layer security in wireless networks

Abstract: Abstract-Nowadays, multimedia application and video streaming have gained a great popularity because of the boasting development on mobile hardware, and battery driven devices have emerged with a tremendous speed. Due to the important issue of battery efficiency on mobile devices, many optimization algorithms have being proposed toward various of battery powered platforms and scenarios. Most of the provided solutions choose to aim at the minimization of energy usage under a given task scheduling by adjusting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Specifically, Taylor et al presented the impact of the legitimate receiver's channel estimation error on the performance of an eigenvector-based jamming technique in [12]. Their research showed that the ergodic secrecy rate provided by the jamming technique decreases rapidly as the channel estimation error increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Taylor et al presented the impact of the legitimate receiver's channel estimation error on the performance of an eigenvector-based jamming technique in [12]. Their research showed that the ergodic secrecy rate provided by the jamming technique decreases rapidly as the channel estimation error increases.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned works in [12][13][14] all used the ergodic secrecy rate to characterize the performance limits of systems. The ergodic secrecy rate is an appropriate secrecy measure for systems in which the encoded messages span sufficient channel realizations to capture the ergodic features of the fading channel [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the CSI of the legitimate user is usually obtained by feedback. A handful of studies under jamming have evaluated the secrecy performance of under imperfect channel estimation for imperfect legitimate channel [241] and for main and jamming links [242], [182], [243]. In addition, these works derive lower or upper bounds, and closed-form expressions for aforementioned scenarios are largely missing in the literature.…”
Section: G Unique Challenges Of Secure Cooperative Jammingmentioning
confidence: 99%
“…Therefore, it is worthwhile investigating the impact of the legitimate receiver's channel estimation error on the secure transmission. Initial works that considered imperfect CSI of the legitimate receiver and no CSI of the eavesdropper can be found in [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Taylor et al presented the impact of the legitimate receiver's channel estimation error on the performance of an eigenvector based jamming technique. Their research showed that the secrecy capacity provided by the jamming technique decreases rapidly as the channel estimation error increases.…”
Section: Introductionmentioning
confidence: 99%